An update on PTEN modulators – a patent review. (2nd November 2019) - Boosani, Chandra S.; Gunasekar, Palanikumar; Agrawal, Devendra K.
ABSTRACT: Introduction : A multitude of cellular and physiological functions have been attributed to the biological activity of PTEN (Phosphatase and tensin homolog) such as inhibiting angiogenesis, promoting apoptosis, preventing cell proliferation, and maintaining cellular homeostasis. Based on whether cell growth is needed to be initiated or to be inhibited, enhancing PTEN expression or seeking to inhibit it was pursued. Areas covered : Here the authors provide recent updates to their previous publication on 'PTEN modulators: A patent review', and discuss on new specificities that affirm the therapeutic potential of PTEN in promoting neuro-regeneration, stem cell regeneration, autophagy, bone and cartilage regeneration. Also, targeting PTEN appears to be effective in developing new treatment strategies for Parkinson's disease, Alzheimer's disease, macular degeneration, immune disorders, asthma, arthritis, lupus, Crohn's disease, and several cancer types. Expert opinion : PTEN mainly inhibits the PI3k/Akt pathway. However, the PI3k/Akt pathway can be activated by other signaling proteins. Thus, novel treatment strategies that can regulate PTEN alone, or combinational treatment approaches that can induce PTEN and simultaneously affect downstream mediators in the PI3K/Akt pathway, are needed, which were not investigated in detail. Commercial interests associated with molecules that regulate PTEN are discussed here, along with limitations and new possibilities to improve them.